2009
DOI: 10.1149/1.3231689
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Long Chain α,ω-Dibromoalkanes at Palladized Solid Cathodes: Homocoupling vs Oligomerization

Abstract: Copper-palladium ͑Cu-Pd͒ and silver-palladium ͑Ag-Pd͒ systems are used as cathode materials for reducing long chain ␣,-dibromoalkanes ͓Br-͑CH 2 ͒ n -Br͔ with n Ͼ 3. Such interfaces globally permit the cleavage of the two C-Br bonds in a single two-electron process. A spectacular potential shift ͑⌬E͒ is obtained in comparison with glassy carbon electrodes at which the total reduction corresponds to a four-electron process. Such potential shifts are typically of the order of 1 V. In particular, cathodic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…On the other hand, the doubly branched ferrocene Fc(C 6 –I) 2 (image B) leads to the appearance of grooves in quite thick layers that could be due to an intermolecular Wurtz-type polymerization process that takes place along with some localized graftings that permits the polymeric form to resist against intensive ultrasonic rinsing. Such anionic polymerization is well-known for α,ω-dihaloalkanes at strongly reducing potentials . We verified that the extent of ferrocene grafting is about 10 times greater for image B than for image A.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…On the other hand, the doubly branched ferrocene Fc(C 6 –I) 2 (image B) leads to the appearance of grooves in quite thick layers that could be due to an intermolecular Wurtz-type polymerization process that takes place along with some localized graftings that permits the polymeric form to resist against intensive ultrasonic rinsing. Such anionic polymerization is well-known for α,ω-dihaloalkanes at strongly reducing potentials . We verified that the extent of ferrocene grafting is about 10 times greater for image B than for image A.…”
Section: Resultssupporting
confidence: 73%
“…Such anionic Langmuir ARTICLE polymerization is well-known for α,ω-dihaloalkanes at strongly reducing potentials. 29 We verified that the extent of ferrocene grafting is about 10 times greater for image B than for image A. Finally, EDX analyses revealed that these polymeric deposits have a high iron content.…”
Section: Resultssupporting
confidence: 64%
“…The immobilization of CO 2 [17], which can be realized on most types of carbons (including graphite and graphene), enables a facile synthesis of poly-carboxylated GC eventually covered with graphene [22]; strongly hydrophilic, such interfaces can be readily transformed into redox materials by simple reactions of the carboxylate group. Also, the use of non-Kolbe oxidation of the polycarboxylate (at + 1.3 V) easily allows [12] the efficient conversion of GC into a poly-electrophilic material with a wide range of interesting reactions that could be regarded as a new chapter in the field of surface electrophilic displacement reactions.…”
Section: Mechanism and Examples Of Surface Functionalizationmentioning
confidence: 99%
“…When required for the investigation of the reduction of benzyl bromide under catalytic conditions, glassy carbon electrodes (GC, surface area of 0.8 mm 2 ) were palladized or silvered. They were obtained following the procedure described in ref . Briefly, prior to metallization, all GC electrodes were carefully polished with silicon carbide paper (Struers) or with Norton polishing paper (types 02 and 03).…”
Section: Methodsmentioning
confidence: 99%